Coast : lifestyle architecture - McCulloch, Janelle (Mulgrave, Vic. : Images Pub., 2011)
Celebrate the beauty of the humble beach house, and the beauty of the beach, in this tribute to seaside shelters, grand and small.
Introduction: Between the sea and the imagination: architecture designed for living on the edge -- Tiny hideaways -- Island refuges -- Family havens -- Unique beach retreats.
Includes index.
Keywords: Seaside architecture -- Pictorial works; Vacation homes -- Pictorial works; Coasts -- Pictorial works